Analysis of the coupling between a single-mode fiber to a multi-core fiber with long-period gratings - Sousa, Liliana (2021)
In this paper, the coupling of a single source injected in a single-mode fiber to all the cores of a multi-core fiber is theoretically studied. The power transfer between the core and the cladding of a fiber is promoted by long-period gratings. To promote the power transfer between the fibers, we considered cladding modes with similar effective refractive index. The results show that the coupling is possible, but the design still needs to be optimized to maximize the power transfer.